The importance of hydraulic architecture to the distribution patterns of trees in a central Amazonian forest - Cosme, Luiza H. M.; Schietti, Juliana; Costa, Flávia R. C.; Oliveira, Rafael S. (The New phytologist, 2017)
Species distributions and assemblage composition may be the result of trait selection through environmental filters. Here, we ask whether filtering of species at the local scale could be attributed to their hydraulic architectural traits, revealing the basis of hydrological microhabitat partitioning in a Central Amazonian forest. We analyzed the hydraulic characteristics at tissue (anatomical traits, wood specific gravity (WSG)), organ (leaf area, specific leaf area (SLA), leaf area: sapwood area ratio) and whole-plant (height) levels for 28 pairs of congeneric species from 14 genera restricted to either valleys or plateaus of a terra-firme forest in Central Amazonia. On plateaus, species had higher WSG, but lower mean vessel area, mean vessel hydraulic diameter, sapwood area and SLA than in valleys; traits commonly associated with hydraulic safety. Mean vessel hydraulic diameter and mean vessel area increased with height for both habitats, but leaf area and leaf area: sapwood area ratio investments with tree height declined in valley vs plateau species. [Correction added after online publication 29 March 2017: the preceding sentence has been reworded.] Two strategies for either efficiency or safety were detected, based on vessel size or allocation to sapwood. In conclusion, contrasting hydrological conditions act as environmental filters, generating differences in species composition at the local scale. This has important implications for the prediction of species distributions under future climate change scenarios.